The Mediation Effect of Customer Perceived Value and AttitudeToward Advertisement on Social Media Influencer’s Credibility on Purchase Intention - Liem Pamela Lukito; Retno Yustini (Soegijapranata Catholic University, 2019)
Instagram isthe most used social mediathat promotes influencer marketing, which is an effective marketing way by using influencer. SMI can be a fashion blogger, such as Gisella who endorses casual fashion in Instagram. SMI’s credibilityhas a role in purchase intention, making a producer consider SMI's credibility when they decide to work with them. Customer perceived value (CPV) can be partially mediating variable toward SMI's credibility on purchase intention, indicating that there might be other variable that act as mediator. Other researcher found that attitude toward advertisement (Aad) act as mediator of SMI's credibility on purchase intention. Thus the purpose of this research is to examine the mediating effect of CPV and Aad toward the SMI's credibility on purchase intention of casual fashion. The population used was female student of SCU Semarang. Descriptive analysis (score tabulation) and statistic analysis (regression, path analysis)were conducted. The result indicated that CPV and Aad are partially mediating SMI's credibility on purchase intention of casual fashion endorsed by Gisella. It implied that producer should screen SMI based on their credibility since it has a great direct effect on purchase intention. Furthermore, they should consider CPV and Aad since it poses a mediating role